BCT401: Introduction to Bio-Composite / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2018)
This course will expose students to the various Bio-composite materials used in the industry. The Bio-composite classes will emphasis on the manufacturing process, application, characteristics and properties of the Bio-composite materials. It is such as basic knowledge that Bio-composite’s student must have